Psychodidae (diptera) of Perú I: Phlebotominae in Huanuco, Pasco and Cusco, its relation to Carrion'disease and dermal leishmaniasis - Cáceres, Abraham G. (2000)
One hundred and twenty species had been reported up to 1999 and the following 11 are now added to Peruvian phlebotomine fauna: Brumptomyia quimperi, Evandromyia sallesi, Lutzomyia fispaili, L. scorzai, L. watsi, Micropygomyia longipennis, Trichophoromyia howardi, T. arevaloi, Trichopygomyia turelli, Warileya euniceae and W. leponti. A complete list of species in Huanuco, Pasco and Cusco departments is included and new records for Ayacucho, Amazonas, Cajamarca, Huancavelica, Junin, La Libertad, Loreto and San Martin are given. There appears to be epidemiological evidences of some phlebotomines of the subgenera Helcocyrtomyia and Pifanomyia as likely vectors of dermal leishmaniosis and Carrion's disease.